Management of Nursing in Preschool Institutions of Ex-Soviet Countries - Feruza Azizova1, Feruza Salomova2, Zilolakhon Adilova3, Ilmira Uruzalieva4, Guloyim Avezova5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Recently,the activity of preschool institutions experiencing dramatic changes, which lead to the emergenceof new requirements for medical care for children. The most important element of health care system isnursery. Current model of nursing is a science and practice aimed to improve the health status of eachchild. The main purpose of this review is to present different approaches of development of an integratedhealth care system in kindergartens used in ex-Soviet countries. Systematization of accumulated experienceand knowledge will help to develop the system theoretical and practical provisions, when the activities ofmedical staff of preschool institutions are determined